To analyse the effect of theraband strenthening with conventional exercise on pain, function & range of motion in patients with adhesive capsulitis - S.HARISHKUMAR; Dr.S.KIRUTHIKA; Dr.R.ARUNACHALAM; Dr.A.KUMERASAN (International Journal of Pharma and Bio Sciences, 2017)
The main aim of this study is to determine effectiveness of Theraband strengthening along with conventional exercise on subjects with Adhesive Capsulitis and to find out the effectiveness of strengthening using Theraband with conventional exercises on subjects with Adhesive Capsulitis and Influence of Theraband training on Pain, Range of Motion and Functional ability. 30 Patients with Adhesive Capsulitis were selected based on the inclusion and exclusion criteria. Group A received Theraband strengthening with Conventional exercise and Group B received Conventional exercise.Range of Motion (ROM) of shoulder is measured using universal goniometer. Pain and Functional ability is quantified with Shoulder Pain And Disability Index as outcome measures.The collected data was tabulated & analyzed using descriptive & inferential statistics. To all parameters mean and standard deviation (SD) were used. Paired t-test was used to analyze significant changes between pre-test and post-test measurements. Unpaired t-test was used to analyze significant changes between two groups. Statistical Analysis of Post test, Pain Index & Disability Index from SPADI scale and Range of Motion from Universal Goniometer revealed that there is high statistically significant difference seen between Group A and Group B. From the result, it is concluded that Theraband strengthening of shoulder along with conventional exercise (GROUP A) is more effective than conventional exercise (GROUP B) in increasing the Range of motion, reduction of Pain and Disability and improve in Functional ability.